The kids are alright - Who (Musical group); Who Films Ltd.; Thorn EMI Video (Firm) (New York : Thorn EMI Video, 1983)
A docu-history of The Who. Features live performances, taped interviews, television appearances from the mid-'60s to the late '70s, and rare promotional films of some of The Who's most popular songs.
VHS format.
"TVF 1082"
Videorecording of the 1979 motion picture.
Executive producer, Sidney Rose ; producers, Tony Klinger, Bill Curbishley ; director, Jeff Stein ; writers, Jeff Stein, Tony Klinger.
The Who.
Keywords: Rock music